Horse and buggy. - (:unkn) unknown (Forsyth County Public Library, 2009)
Photo taken in the 1910s.
Horse and buggy.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth